Reality TV : realism and revelation - Biressi, Anita, 1965-; Nunn, Heather (Wallflower Press, 2005)
This book analyses new and hybrid genres of television including observational documentaries, talk shows, game shows, docu-soaps, dramatic reconstructions, law and order programming and 24/7 formats such as Big Brother and Survivor.